Biodiesel and fossil-fuel diesel soot oxidation activities of Ag/CeO2 catalyst. (15th August 2019) - Corro, Grisel; Flores, Angel; Pacheco-Aguirre, Francisico; Pal, Umapada; Bañuelos, Fortino; Ramirez, Araceli; Zehe, Alfred
Graphical abstract: Highlights: Soots from diesel, biodiesel and diesel/biodiesel blends combustion were investigated. Soots were characterized by BET, SEM, and FTIR, Raman and DRX spectroscopies. Biodiesel reduced soot trends of diesel. Biodiesel addition to diesel generates soots which get oxidized at lower temperature. 3%Ag/CeO2 is very active catalyst for oxidizing the biodiesel/diesel soots. Abstract: We present the effects of the addition of biodiesel, derived from waste frying oil, to fossil-fuel diesel, on soot emissions, and on the physicochemical properties of soot particles. Biodiesel was blended with diesel to study the sooting trend of the blended fuel, and the effect of the chemical composition of soot generated from the blended fuel combustion on its reactivity during catalytic oxidation over reduced 3%Ag/CeO2 . The emitted soots were characterized by their specific surface areas, SEM, and FTIR, Raman and DRX spectroscopies. The catalyst was characterized by UV–vis optical absorption, XPS and DRX spectroscopy. The composite catalyst showed excellent activity for the oxidation of the soots generated from the combustion of pure diesel, pure biodiesel and diesel-biodiesel blend (50% by volume of each). However, soot generated from pure biodiesel and diesel-biodiesel blend combustion showed higher reactivity for catalyzed oxidation than pure diesel soot. The activity of the catalyst was correlated with the metallic state of Ag at its surface, and with the chemical characteristics of the soot particles generated during the combustion of different fuels. We demonstrate that along with reducing the sooting tendency of diesel, biodiesel addition also leads to soots that are easier to oxidize in particulate filters in diesel engines.